A tough woman around tender men: Dilma Rousseff, gendered double bind, and misogynistic backlash - Jalalzai, Farida; Kreft, Brianna; Martinez-Port, Lizbet; dos Santos, Pedro A. G.; Smith, Brigid M. (Frontiers in Political Science, 2022)
Dilma Rousseff's presidency ended in controversial form. The first woman elected to the position in Brazil, Rousseff's 2016 impeachment was seen as a coup by her supporters and as a necessary step for democracy by her detractors. With the Brazilian economy facing its worst recession in history and the Car Wash corruption scandal ravaging the political class, critics continually raised questions about Rousseff's leadership style and abilities. This article analyzes how this criticism in part can be attributed to gendered subjective understandings of preferred leadership traits. Using a thematic analysis of interviews with political actors in five different Brazilian states conducted in 2017 and 2018, we demonstrate that gender stereotypes and sexism fueled criticisms about women's political leadership. While Rousseff's presidency was riddled with problems, the president's leadership style and abilities were scrutinized in distinct gendered ways, indicating a gendered double bind and a backlash against women in politics.